Trade-based money laundering and domestic resource mobilization in oil-exporting Countries - Joshua Adeyemi Afolabi; Musibau Adetunji Babatunde (Journal of Economic Criminology)
The rapid evolution of global trade offers great productivity gains to participating countries but also raises the likelihood of losing domestic resources through trade-based money laundering. This paper empirically examined whether trade-based money laundering affects domestic resource mobilization in nine selected Organization of Petroleum Exporting Countries (OPEC) member states from which panel data spanning 2009–2018 were obtained. The panel quantile regression estimator was used to analyze the data. The empirical result showed that trade-based money laundering reduces government revenue and weakens the ability of the government to mobilize domestic resources to fulfil its fiscal responsibilities. The magnitude of impact exhibits an increasing trend as the adverse effect is more pronounced in countries with high domestic resources and less severe in countries with low domestic resources. Therefore, policymakers and governments of OPEC member states should design and ensure the effective implementation of anti-money laundering policies to tame trade-based money laundering.